2018
DOI: 10.3390/act7040087
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Shaftless Semi-Hard Magnetic Material Flywheel on Radial Hysteresis Self-Bearing Drives

Abstract: Flywheel Energy Storage Systems are interesting solutions for energy storage, featuring advantageous characteristics when compared to other technologies. This has motivated research effort focusing mainly on cost aspects, system reliability and energy density improvement. In this context, a novel shaftless outer-rotor layout is proposed. It features a semi-hard magnetic FeCrCo 48/5 rotor coupled with two bearingless hysteresis drives. The novelty lies in the use of the semi-hard magnetic material, lending the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Sandia National Lab [111,112] is working on improving flywheel energy density with graphene to increase the flywheel's strength. Circosta et al [113] present a semi-hard magnetic FeCrCo 48/5 rotor that enables the use of bearingless hysteresis drives. Low-cost materials, such as concrete, are also being used.…”
Section: New Materialsmentioning
confidence: 99%
“…Sandia National Lab [111,112] is working on improving flywheel energy density with graphene to increase the flywheel's strength. Circosta et al [113] present a semi-hard magnetic FeCrCo 48/5 rotor that enables the use of bearingless hysteresis drives. Low-cost materials, such as concrete, are also being used.…”
Section: New Materialsmentioning
confidence: 99%
“…The FESS with self-bearing hysteresis drive was proposed for the satellite energy system, and the vibration performance of the satellite flywheel rotor was tested. The results showed that the magnetic suspension system could satisfy performance at the maximum speed of the flywheel rotor [12]. However, the effective vibration control method of the rotor shaft was not designed for the FESS.…”
Section: Introductionmentioning
confidence: 98%
“…Combining the actuation and rotor support, Active Magnetic Bearings (AMBs) can be used to mitigate vibrations for high speed machines, offering improved performance, even though they require the inclusion of amplifiers and sensors to control the rotor levitation. Indeed, AMBs have a much higher life expectancy compared to rolling element bearings, together with having a lubrication-free architecture particularly well suited to wide temperature ranges [22], operation in a vacuum and very high speed applications, such as flywheels [23,24]. The closed loop nature of AMB levitation allows tailoring of the controller to suit a given application, for example, with custom stiffness, damping and unbalance rejection [25,26].…”
Section: Introductionmentioning
confidence: 99%